Sustainable Illumination as a Catalyst for Change: The Broader Impacts of the Ponto Iluminado Initiative - De Moraes, Thiago Matheus Martins [UNESP]; Murad, Leonardo Oliveira [UNESP]; De Lima Viveiros, Henrique Amon [UNESP]; Ballestieri, Jose Antonio Perrella [UNESP]; Dias, Rubens Alves [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The Ponto Iluminado Initiative, centred on sustainable lighting, has evolved significantly, impacting both the community and the scientific field. This article examines how the Initiative's actions, focused on lighting systems, promote socio-environmental benefits and scientific advancements. Starting with the implementation of Brazil's first bus stop powered by photovoltaic energy, it expanded into areas such as energy efficiency, waste management, water conservation, and environmental education, always with lighting as the central pillar. Educational activities include initiatives in schools and universities, promoting rational energy use and sustainability awareness, while also studying barriers in energy planning. The project also engages volunteers, teaching sustainability and efficiency practically, offering a new perspective on resource utilization.
Keywords: barriers; education; energy efficiency; energy planning; sustainable lighting